Effects of Selected Corporate Governance Characteristics on Firm Performance: Empirical Evidence from Kenya - Vincent Okoth Ongore; Peter Owoko K'Obonyo (International Journal of Economics and Financial Issues, 2011)
This paper examines the interrelations among ownership, board and manager characteristics and firm performance in a sample of 54 firms listed at the Nairobi Stock Exchange (NSE). These governance characteristics, designed to minimize agency problems between principals and agents are operationalized in terms of ownership concentration, ownership identity, board effectiveness and managerial discretion. The typical ownership identities at the NSE are government, foreign, institutional, manager and diverse ownership forms. Firm performance is measured using Return on Assets (ROA), Return on Equity (ROE) and Dividend Yield (DY). Using PPMC, Logistic Regression and Stepwise Regression, the paper presents evidence of significant positive relationship between foreign, insider, institutional and diverse ownership forms, and firm performance. However, the relationship between ownership concentration and government, and firm performance was significantly negative. The role of boards was found to be of very little value, mainly due to lack of adherence to board member selection criteria. The results also show significant positive relationship between managerial discretion and performance. Collectively, these results are consistent with pertinent literature with regard to the implications of government, foreign, manager (insider) and institutional ownership forms, but significantly differ concerning the effects of ownership concentration and diverse ownership on firm performance.